Experimental and numerical investigation of the effects of stacking sequence and stress ratio on fatigue damage of glass/epoxy composites. (15th January 2017) - Roundi, Walid; El Mahi, Abderrahim; El Gharad, Abdellah; Rebière, Jean-Luc
Abstract: In the present paper fatigue behavior of glass/epoxy composite materials under different stress ratios and for various plies orientation angles has been established. Experimental and numerical analysis (Finite Element Method) were performed on various specimens subjected to cyclic tensile tests in order to outline the influences of stress ratios and the stacking sequence ([02 /902 ]s ; [902 /02 ]s ; [03 /90]s ; [903 /0]s ) on glass/epoxy fatigue properties. Static analysis is done experimentally to identify the stress-strain diagrams, strain to failure, Young's modulus and tensile strength for each stacking sequence. Comparison between experimental and numerical prediction show good agreement. The Results of this investigation can lead us to choose the most optimal stacking sequence for giving boundary conditions to achieve the maximum fatigue life.